Regulatory Dendritic Cells Induced by K313 Display Anti-Inflammatory Properties and Ameliorate Experimental Autoimmune Encephalitis in Mice - Zhou, Yan; Leng, Xiao; Luo, Xingyan; Mo, Chunfen; Zou, Qiang; Liu, Yang; Wang, Yantang (Frontiers in Pharmacology, 2020)
As a GSK-3β inhibitor reported by our group, K313 is a novel benzoxazole derivative and displays anti-inflammatory properties in RAW264.7 macrophages without cytotoxicity. The activity of GSK-3β affects the differentiation and maturation of bone marrow-derived dendritic cells (BMDCs). This study aims to investigate whether K313 can be used to induce regulatory/tolerogenic dendritic cells (DCregs), and the therapeutic effects of DCregs induced by K313 in the autoimmune model of experimental autoimmune encephalitis (EAE). The results show that compared with LPS stimulated mature DCs, K313-treated BMDCs display obvious tolerogenic characteristics with decreased expression of co-stimulatory molecules, downregulated secretions of pro-inflammatory cytokines and unregulated secretion of anti-inflammatory cytokine IL-10. The above characteristics conform to the typical phenotypes of DCregs. Moreover, K313-modified DCregs inhibit antigen-specific T cell responses in vitro. Furthermore, by adoptive transfer, K313 modified DCregs to the EAE mice, and the development of disease was ameliorated to some extent. In addition, treatment with K313-modified DCregs also significantly reduced the percentages of splenetic Th1 and Th17 cells and increased the percentage of Tregs in EAE mice. In conclusion, K313-modified DCregs show anti-inflammatory properties in vitro and have a significant positive effect on the EAE disease in vivo. Our data indicate that K313-induced DCregs pulsed with auto-antigen might have potential use as a therapeutic approach for autoimmune inflammation of the central nervous system.